Hoarseness Due to Aortic Arch Aneurysms - Yuan,Shi-Min (2020)
Abstract Objective: To give an overview of the Ortner’s syndrome caused by an aortic arch aneurysm. Methods: By comprehensive retrieval of the pertinent literature published in the past two decades, 75 reports including 86 patients were collected and recruited into this study along with a recent case of our own. Results: The aortic arch aneurysms causing hoarseness were most commonly mycotic aneurysms. In this patient setting, in addition to the left recurrent laryngeal nerve, trachea was the most commonly affected structure by the aortic arch aneurysm. Surgical/interventional/hybrid treatments led to a hoarseness-relieving rate of 64.3%, much higher than that of patients receiving conservative treatment. However, hoarseness recovery took longer time in the surgically treated patients than in the interventionally treated patients. Conclusion: The surgical and interventional treatments offered similar hoarseness-relieving effects. Surgical or interventional treatment is warranted in such patients for both treatment of arch aneurysms and relief of hoarseness.